Language management and language work in a multilingual call center: An ethnographic case study - Woydack, Johanna (Revista Internacional de Organizaciones, 2019)
Drawing on long-term ethnography and interviews, this paper investigates language work and language management in the context of a multilingual call center. It looks at how language issues are managed on a day-to-day basis, specifically in three areas that have been previously overlooked: i) the recruitment process for multilingual agents, ii) how agents are trained in language management, and iii) how their performance on the phone in multiple languages is evaluated and monitored. The paper re-examines the value of scripts, particularly in relation to knowledge management, challenging the idea that working language fluency on the phone is the principal skill required. Rather, the paper demonstrates that successful agents utilize a variety of skills which are learned with the help of scripts, concluding that 'interactive professional' rather than 'language worker' better describes the skill set required by agents for this work.